2018
DOI: 10.1088/1361-6528/aae9b3
|View full text |Cite
|
Sign up to set email alerts
|

Robust, reproducible, recyclable SERS substrates: monolayers of gold nanostars grafted on glass and coated with a thin silica layer

Abstract: We prepared and characterized recyclable surface enhanced Raman spectroscopy (SERS) active glass chips. Gold nanostars were grafted on properly functionalized glasses by means of electrostatic interactions and then they were coated with a silica layer of controllable thickness in the nanometer range. The SERS activity of the obtained substrates were tested in terms of reproducibility and homogeneity intra-samples and inter-samples from different batches using the Raman reporter as the model compound rhodamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…We used the same laser wavelength and light power (632.8 nm and 1.5 × 10 5 W/cm 2 ), same integration times (20 s) and same objective magnification (50×). As already explained in our previous paper [17] to derive a reliable EF value it is important to evaluate the scattered volumes in the two experiments and considering that the SERS signal decreases dramatically with distance vanishing beyond 10–20 nm. In the present case the ratio between the scattering volumes in Raman and SERS experiments is approximately equal to 2 × 10 3 .…”
Section: Methodsmentioning
confidence: 99%
“…We used the same laser wavelength and light power (632.8 nm and 1.5 × 10 5 W/cm 2 ), same integration times (20 s) and same objective magnification (50×). As already explained in our previous paper [17] to derive a reliable EF value it is important to evaluate the scattered volumes in the two experiments and considering that the SERS signal decreases dramatically with distance vanishing beyond 10–20 nm. In the present case the ratio between the scattering volumes in Raman and SERS experiments is approximately equal to 2 × 10 3 .…”
Section: Methodsmentioning
confidence: 99%
“…SERS as a technique for pesticide detection has been cited in several studies, and has shown promising results to be a rapid method that could even detect analytes at trace amounts. Several materials and morphologies have been explored with this particular application in mind—Ag nanoflowers [18], Au/Ag nanorods [14], and colloidal Au nanoparticles [19] among others, all of which showed capabilities of detecting low pesticide concentrations, down to 10 −10 M. However, aside from sensitivity, there are still more factors to consider in this particular application, such as the reproducibility of results and the capability of the substrates to detect multiple pesticides in real food matrices [20,21]. To address these issues, morphology control and material selection have been given emphasis, focusing on achieving large-scale uniformity in obtaining SERS measurements [22].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the shortage, some reproducible preparations of clean and highly Ag and Au SERS active substrates have been reported in Reference [14]. Bassi et al [15] prepared recyclable SERS active glass chips. The gold nanostars were grafted on functionalized glasses by means of electrostatic interactions and then they were coated with a silica layer of controllable thickness.…”
Section: Introductionmentioning
confidence: 99%